2023
DOI: 10.3390/curroncol30030219
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Proton Therapy for Locally Advanced Breast Cancer: Clinical and Technical Considerations

Abstract: Proton therapy is a promising therapeutic modality with unique physical properties that allow for abrupt dose fall-off distal to the target of interest, thereby sparing nearby organs at risk. A number of studies have identified the utility of proton radiation in mitigating treatment related sequelae for patients with locally advanced breast cancers. Thus, in the following review, we highlight clinical and technical considerations for proton radiotherapy delivery in patients with locally advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Since the early 2000s, proton therapy was suggested as a promising technique for breast cancer treatment and several studies have shown potential benefits for toxicity reductions compared to radiotherapy using photons [10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 2000s, proton therapy was suggested as a promising technique for breast cancer treatment and several studies have shown potential benefits for toxicity reductions compared to radiotherapy using photons [10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inviting experts to review and resolve controversial themes for this Special Issue, we also solicited descriptions of innovative topics positioned at the vanguard of breast radiotherapy. Lalani et al discussed the potential of proton therapy in the management of locally advanced breast cancer [15]. These authors reviewed the unique physical characteristics of proton beams, which may constitute a distinct advantage when clinicians are beset by the need to encompass nodal basins and intricate reconstructions.…”
mentioning
confidence: 99%